2022
DOI: 10.3390/vaccines10030428
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination among Czech Dentists

Abstract: This work describes and evaluates vaccination against COVID-19 among members of the Czech Dental Chamber during the pre-booster vaccination phase. A cross-sectional online survey was conducted between 23 June and 4 September 2021, among 2716 participants, representing 24.3% of all chamber members. A total of 89.5% of respondents stated that they were registered for vaccination against COVID-19, their vaccination had started or been completed, or had a medically relevant reason to avoid vaccination. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Following the pandemic, most respondents to our questionnaire (80.36%) declared themselves vaccinated against SARS-CoV-2 infection. This is in accordance with previously published data [ 14 , 15 , 16 ]. Among them, almost all (96.67%) applied the questionnaire for epidemiological triage to each patient, but 8 out of 10 did not test the patient upon entering the office.…”
Section: Discussionsupporting
confidence: 94%
“…Following the pandemic, most respondents to our questionnaire (80.36%) declared themselves vaccinated against SARS-CoV-2 infection. This is in accordance with previously published data [ 14 , 15 , 16 ]. Among them, almost all (96.67%) applied the questionnaire for epidemiological triage to each patient, but 8 out of 10 did not test the patient upon entering the office.…”
Section: Discussionsupporting
confidence: 94%
“…In a study conducted in the Czech Republic, 79.6% of dentists surveyed stated they were fully vaccinated. The more positive attitude to vaccination against COVID-19 among dentists could be attributed to their type of training [18]. Abedin et al showed that a general population with a higher level of education has a more positive attitude towards vaccination [19].…”
Section: Discussionmentioning
confidence: 99%
“…The data in this letter are based on COVID-19 prevalence and COVID-19 vaccination data of Czech dentists and the Czech general population. The dentist-related data were obtained from studies performed and published by the authors in 2021 and 2022, and the Czech general population data were mined from the Our World in Data online database [6,7,12,13]. In both groups, only cases confirmed by PCR test were included.…”
Section: Data Collectionmentioning
confidence: 99%
“…As such, they may serve as a suitable subpopulation of healthcare workers to demonstrate the effect of priority vaccination. Czech dentists are one of the best epidemiologically described professional groups during the COVID-19 pandemic and, so far, have shown a very high willingness to be vaccinated [6,7]. Additionally, Czech dentistry remained highly operative even during the pandemic [8].…”
Section: Introductionmentioning
confidence: 99%